2021
DOI: 10.1080/17425247.2021.1867096
|View full text |Cite
|
Sign up to set email alerts
|

Wound dressings as growth factor delivery platforms for chronic wound healing

Abstract: Introduction: Years of tissue engineering research have clearly demonstrated the potential of integrating growth factors (GFs) into scaffolds for tissue regeneration, a concept that has recently been applied to wound dressings. The old concept of wound dressings that only take a passive role in wound healing has now been overtaken, and advanced dressings which can take an active part in wound healing, are of current research interest. Areas covered:In this review we will focus on the recent strategies for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
50
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(55 citation statements)
references
References 198 publications
0
50
0
Order By: Relevance
“…Further studies are underway on the activity of the CHIT/HEGF composites applied to in vivo wound models for the evaluation of EGF release and its effects on wound progression. [20] Preliminary biological investigations were performed to evaluate the occurrence of any cytotoxic effects and the ability of CHIT/HEGF dressing to support fibroblast viability, with respect to CHIT scaffold, whose cytocompatibility had been previously demonstrated. [12] The in vitro cytotoxicity evaluation is a fast method to provide predictive evidence of material biocompatibility.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Further studies are underway on the activity of the CHIT/HEGF composites applied to in vivo wound models for the evaluation of EGF release and its effects on wound progression. [20] Preliminary biological investigations were performed to evaluate the occurrence of any cytotoxic effects and the ability of CHIT/HEGF dressing to support fibroblast viability, with respect to CHIT scaffold, whose cytocompatibility had been previously demonstrated. [12] The in vitro cytotoxicity evaluation is a fast method to provide predictive evidence of material biocompatibility.…”
Section: Resultsmentioning
confidence: 99%
“…By introducing EGF sequence within the backbone of HELP, we obtained a fusion protein (HEGF) maintaining both the EGF bioactivity and the responsivity to a proteolytic environment, such as a wound site. [20] The study reported here focuses on the development of a new composite scaffold that combines the flexibility of the 3D printing technique with the stimuli-induced release ability of a HEGF hydrogel. High-porosity chitosan 3D-printed scaffolds (CHIT) were embedded by enzymatic cross-linking in HEGFenriched HELP matrix and the interaction between these components as well as the release of EGF from the scaffold was evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, another traditional approach for chronic wound therapy is via fish skin acellular treatment [ 4 ]. This method is considered as one of the significant treatments due to its histological properties that promote cellular regulation and is rich with omega-3 fatty acids to supply to the local tissue [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Wound healing is a dynamic and complex process that initiates the immune response for tissue repair [ 5 ]. Several types of wounds, including vascular ulcers, pressure ulcers, and diabetic ulcers, are primarily categorized as chronic wounds [ 6 ]. The abnormal pathological conditions of chronic wounds lead to a poor healing rate or excessive scar formation after recovery.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, clinical researchers have recently explored the efficiency of certain new therapies for DFUs, such as punch grafting, negative pressure wound therapy, and magnetic fields [ [8] , [9] , [10] ]. In addition, considerable research has been conducted for promoting wound healing, among which the local application of growth factors, such as β-fibroblast growth factor (β-FGF), epidermal growth factor (EGF), and vascular endothelial growth factor (VEGF), can significantly accelerate wound healing [ [11] , [12] , [13] , [14] , [15] ]. However, there also exist certain challenges that limit the local application of growth factors in chronic wounds, such as high dose requirements, protein instability and its short lifetime in vivo, and high cost [ 16 ].…”
Section: Introductionmentioning
confidence: 99%